A new species of terrestrial frog of the genus Noblella Barbour, 1930 (Amphibia: Strabomantidae) from the Llanganates-Sangay Ecological Corridor, Tungurahua, Ecuador - Reyes-Puig, Juan (2019)
We describe a new species of terrestrial frog of the genus Noblella from the eastern versants of the Ecuadorian Andes in the upper Pastaza watershed. Noblella naturetrekii sp. n. differs from its Ecuadorian congeners by the presence of a differentiated tympanic membrane and a weakly defined tympanic annulus, and eyelids with rounded tubercles. In addition, the new species is characterized by its blackish-dark brown ventral coloration scattered with little white dots and the absence of papillae at the tip of the fingers and toes. We provide a detailed description of the call and osteology of the new species. Finally, we present the most complete phylogeny of the genus, which confirms that Noblella is a non-monophyletic group.